ETHNOGRAPHY STUDY: SHARED VALUE BETWEEN MINANG MIDWIFE CLASS OF 1968, SEKOLAH PERAWAT BIDAN PADANG - Oci Citra Maharani; Irma Nur Wanty; Jerry Heikal (Jurnal Media Akademik (JMA), 2024)
Indonesia as a nation consists of several islands with different tribes, cultures, and multiple ethnicities. One of them is the Minang tribe. Located on Sumatra Island, Minang people famous for its hard-working, food, culture and mostly the Minang people are working as a traders (pedagang) or as businessmen. Also due to their personal needs a lot of Minang people becoming a wanderer, they are looking for a better opportunity and experience by wandering to other island and due to that currently Minang people are becoming more varied in terms of occupation. Not only in men also in women, one of the occupations for Minang women is becoming a midwife. This study aims to understand the value shared by Minang women who occupied as a midwife, in terms of behaviour, belief, and culture. By using qualitative research with the Ethnographic method. Data collection was carried out by doing in-depth interviews, life history, and documentary data.